2015
DOI: 10.1007/s10067-015-2913-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of home-based exercise intervention on health-related quality of life for patients with ankylosing spondylitis: a meta-analysis

Abstract: The objective of this paper was to objectively evaluate the effectiveness of home-based exercise interventions for improving health-related quality of life in patients with ankylosing spondylitis (AS). Databases including PubMed, Web of Science, EMBASE, Ovid-Medline, and The Cochrane Library were electronically searched published from inception through October 2014 involving home-based exercise intervention in AS patients. Studies that measured the Bath Ankylosing Spondylitis Functional Index (BASFI), the Bath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 28 publications
3
39
0
2
Order By: Relevance
“…Additional use of qualitative methods, like semistructured interviews with patients to get insight into potential barriers and facilitators, could be of value before actual implementation. Second, despite the known effects of exercise on psychosocial well‐being , questions on perceived effects of SGE only addressed physical health. It is, however, conceivable that our observation that patients (on average) participate in SGE for many years is related to perceived positive effects that go beyond physical functioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional use of qualitative methods, like semistructured interviews with patients to get insight into potential barriers and facilitators, could be of value before actual implementation. Second, despite the known effects of exercise on psychosocial well‐being , questions on perceived effects of SGE only addressed physical health. It is, however, conceivable that our observation that patients (on average) participate in SGE for many years is related to perceived positive effects that go beyond physical functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Regular exercise is considered to be a key component in the management of axial SpA and has been shown to reduce disease activity, pain, and stiffness and improve physical functioning, chest expansion, spinal mobility, and cardiorespiratory function in patients with axial SpA . Additionally, regular exercise has the potential to reduce depressive symptoms . With supervised group exercise (SGE), greater improvements in quality of life, spinal mobility, and patient global assessment were achieved as compared to unsupervised, individual exercise programs .…”
Section: Introductionmentioning
confidence: 99%
“…A total of six studies comprising 1098 participants were included in the study. Meta‐analyses showed that home‐based exercise interventions significantly reduced the BASFI scores (MD = −0.39, 95% CI: −0.57, −0.20, P = 0.001), BASDAI scores (MD = −0.50, 95% CI: −0.99, −0.02, P = 0.04) and depression scores (MD = −2.31, 95% CI: −3.33, −1.30, P = 0.001), Thus, home‐based exercise interventions can effectively improve the health‐related quality of life in patients with AS (Liang et al., ).…”
Section: Musculo‐skeletal Disordersmentioning
confidence: 98%
“…There are no studies evaluating the impact of exercise on bone mineral density in patients with ankylosing spondylitis; however, improvements in disease activity and physical function have been noted in patients with AS who participate in exercise programs [58,59]. Recent consensus guidelines also encourage consistent physical activity and stretching in patients with AS [60].…”
Section: Treatmentmentioning
confidence: 99%